(untitled) (Almanack, 2023)
This article surveys the scholarly contributions in the Almanack Braziliense and the Almanack, paying particular attention to new research on the political culture of constitutionalism and early constitutionalist practice. Beginning in 2005, these contributions, in formats ranging from scholarly articles to presentations and exchanges on YouTube, show how in Brazil people from a range of social groups and with diverse political aims and projects reckoned with questions of rights and representation in the context of local, regional, and transatlantic crises to forge the end of Portuguese rule in America.